Impaired Modulation of Corticospinal Excitability in Drug-Free Patients With Major Depressive Disorder: A Theta-Burst Stimulation Study - Vignaud, Philippe; Damasceno, Caroline; Poulet, Emmanuel; Brunelin, Jérôme (Frontiers in Human Neuroscience, 2019)
Impaired neural plasticity may be an important mechanism in the pathophysiology of major depressive disorder (MDD). Coupled with electromyography, repetitive transcranial magnetic stimulation (rTMS) is a useful tool to evaluate corticospinal excitability and cortical neuroplasticity in living humans. The goal of this study was to compare rTMS-induced cortical plasticity changes in patients with MDD and in healthy volunteers. In this single-blind controlled study, 11 drug-free patients with MDD and 11 matched healthy controls were included. Cortical excitability, measured by the amplitude of motor evoked potentials (MEPs) evoked by single-pulse TMS, was assessed before and repeatedly after (for 30 min) participants received a single session of intermittent (iTBS) and continuous theta-burst stimulation (cTBS). rTMS was applied over the left motor cortex using a neuronavigation system. Intensity was set at 80% of the active motor threshold. A large interindividual variability was observed after both iTBS and cTBS in the 2 groups. At the group level, we observed impaired iTBS-induced neuroplasticity in patients with MDD compared to that in controls. No differences were observed between the groups regarding cTBS-induced neuroplasticity. Our results suggest impaired long-term potentiation (LTP)-like mechanisms in MDD but preservation of long-term depression (LTD)-like mechanisms. clinicaltrials.gov identifier: NCT02438163.